Low birth weight and cardiovascular risk in a Portuguese sample - Frutuoso, J. (2016)
The aim was to evaluate whether it had a similar effect in a Portuguese sample and if low weight classes – low weight (LW <2500g), very low weight (VLW <1500g) and extremely low weight (ELW <1000g) – had statistically significant differences between them.